Traumatic pneumothorax and hemothorax - Bergalli, Luis (Cirugía del Uruguay, 1974)
To understand the physiopathology of pleural occupation, it is necessary to briefly review ali the possible traumatic contingencies. which may be present in thoraxic contusions. Based on the study of 45 patients with serious injuries, 95 % of which presented abnormal pleural occupation, the authors explained the therapy app!i.ed. This depends on the general condition of the patient, of the possible consequences to the injured party and the magnitude of the hemorrhage. An hemopneumothorax is, in itself, a systematic indication of intercostal drainage_ But simple pneumothorax and hemothorax will depend on the degree of their extension. The technical methods used to perform drainage are explained. Emphasis is placed on the manner in which thoracotomy shiuld be performed in traumatized patients, and the different forms of approach are described.